California Elected Women's Association for Education and Research Third Annual Meeting (1977)
This program outlines the Third Annual Meeting of the California Elected Women's Association for Education and Research, held May 13–14, 1977, in Coronado, California. The two-day agenda includes panel discussions and general sessions on topics such as affirmative action, women's leadership, property tax reform, juvenile justice, housing, and cross-cultural perspectives on women, along with the election of officers and a business meeting. Featured speakers include local and state officials, academics, and Congresswoman Yvonne Brathwaite Burke, reflecting the organization's focus on policy, governance, and women's leadership.